Analytical Comparison of Core Competencies across Civil Engineering Positions within New England Department of Transportation Agencies. Issue 1 (January 2019) - Ryan, Alyssa; Bouchard, Chelsea; Fitzpatrick, Cole; Knodler, Michael; Ahmadjian, Christopher
As many within the current transportation workforce approach retirement and the industry transitions into the 21st century, there are two notable challenges: 1) the incredible wealth of institutional knowledge that will be leaving the workforce, and 2) the continued increase in the application of new technologies, skills, and knowledge of the entering workforce. A resulting impact of these issues is that the gap between old and new employee competencies and skills is widening; therefore, there is a specific need and opportunity to develop new job competencies which address these changes. This research evaluates existing Department of Transportation (DOT) job specifications and job postings for civil engineers at various levels in the transportation industry within the New England region. Each job specification and posting was gathered and reviewed for specific competencies in accordance with the Bureau of Labor Statistics (BLS) core competencies and the American Association of Engineering Societies' (AAES) competency model. Further, licensure requirements, including the Engineer-In-Training (EIT) and Professional Engineer (PE) certifications, were gathered. The quantitative analysis resulted in several notable competency gaps (or inconsistencies) between job positions across the DOTs, as well as gaps in both the BLS and AAES competency models. Additionally, the analysis of job position licensure requirements presented further significant gaps between the DOT agencies. This research provides a foundation from which to develop competencies for civil engineering positions at state DOTs and other agencies, one that is reflective of a more dynamic and sustainable transportation workforce that will excel throughout the 21 st century.